(untitled) (AmeriQuests, 2014)
On 13 February 2010, in Via Padova, a multicultural area of Milan, a young Egyptian was stabbed and killed by native of the Dominican Republic. After the murder, several members of the city’s North African community exploded in a running street riot. The events were followed by a harsh political debate, leading to two bylaws were issued by the Mayor of Milan, which sought to impose severe restrictions on life in the area. These two bylaws, N°14/2010 and N°15/2010, are part of a wave of administrative acts about urban security that were approved by different local governments in Italian cities, after the birth of the “Security Emergency” in 2006-2008. These measures can’t be considered traditional means of law enforcement in Italy: the municipal bylaws are administrative acts approved by local government of each city without any direct link to the Parliament or the Central Government. Although public order is competence of the Central Government, since the early 90s local governments claimed more power in order to deal with urban security. Moreover, in 2009 was approved a specific group of regulations, the “Pacchetto sicurezza” that increased the controls on immigration in the cities by police, the army and citizens’ participation “ronde cittadine”. This is something new in the field of immigration control in Italy: moving from the national borders, control on immigration comes in the cities and in the neighbourhoods. This paper firstly depicts the new powers of local governments dealing with urban security as they move beyond the traditional limits of Law enforcement, and provides descriptions of the army and private citizens as new actors of urban social control against immigration. Secondly, the case of Via Padova is taken as a concrete example of administrative acts in the realm of urban security that create a “state of exception” in a specific neighbourhoods, targeting the immigrants and the places where they gather. The link between this exceptional situation and the Zero Tolerance approach that supported the measures creates a space where the legal aspect of security administrative acts is ambiguous: the Milan bylaws can be considered as an actual mechanism to move beyond the traditional criminalization of immigrants.